Cost‐effectiveness of chemoradiation followed by esophagectomy versus chemoradiation alone in squamous cell carcinoma of the esophagus. (20th November 2019) - Salcedo, Jonathan; Suen, Sze‐chuan; Bian, Shelly X.
Abstract: Background: Standard treatment for locally advanced esophageal cancer usually includes a combination of chemotherapy, radiation, and surgery. In squamous cell carcinoma (SCC), recent studies have indicated that esophagectomy after chemoradiation does not significantly improve survival but may reduce recurrence at the cost of treatment‐related mortality. This study aims to evaluate the cost‐effectiveness of chemoradiation with and without esophagectomy. Methods: We developed a decision tree and Markov model to compare chemoradiation therapy alone (CRT) versus chemoradiation plus surgery (CRT+S) in a cohort of 57‐year‐old male patients with esophageal SCC, over 25 years. We used information on survival, cancer recurrence, and side effects from a Cochrane meta‐analysis of two randomized trials. Societal utility values and costs of cancer care (2017, USD) were from medical literature. To test robustness, we conducted deterministic (DSA) and probabilistic sensitivity analyses (PSA). Results: In our base scenario, CRT resulted in less cost for more quality‐adjusted life years (QALYs) compared to CRT+S (154 082 for 1.32 QALYs/patient versus 165 035 for 1.30 QALYs/patient, respectively). In DSA, changes resulted in scenarios where CRT+S is cost‐effective at thresholds between 100 000‐150 000/QALY. In PSA, CRT+S was dominant 17.9% and cost‐effective at willingness‐to‐pay of 150 000/QALY 38.9% of the time, and CRT was dominant 30.6% and cost‐effective 61.1% of the time. This indicates that while CRT would be preferred most of the time, variation in parameters may change cost‐effectiveness outcomes. Conclusions: Our results suggest that more data is needed regarding the clinical benefits of CRT+S for treatment of localized esophageal SCC, although CRT should be cautiously preferred. Abstract : We use a Markov model informed by event rates, costs, and utilities from medical literature to show the addition of esophagectomy to definitive chemoradiation is unlikely to be cost‐effective for elderly US males with esophageal squamous cell carcinoma (SCC). However, additional clinical studies on esophagectomy outcomes in SCC are necessary to preclude surgery in all contexts.